Lung-sparing resection instead of pneumonectomy in patients with wide spread lung cancer - Moroz, Gennady S. (Radiology and oncology (Ljubljana), 1997)
The 5-year survival rate of the patients after lung-sparing resection (Group A) was 18.2% vs. 15.9% after pneumonectomy (Group B) (p>0.05). Recurrences were detected in 63.6% of patients of group A vs. 56.9% in patients of group C(after lob - bilobectomy) (p>0.05).
Keywords: Lung neoplasms; Neoplasm invasiveness; Neoplasm staging; Pneumonectomy; Surgery; Survival analysis